Making your own way: A grounded theory study of how parents of children with autism navigate intervention - Gentles, Stephen James (My University, 2015)
Parents of children with autism shoulder substantial responsibility for navigating intervention to address autism-related concerns, and face conditions of high uncertainty and stress to do so. There is a lack of holistic research explaining how parents cope and respond to the complexity and obstacles that characterize their situation as they navigate multiple forms of intervention across multiple systems of care. The purpose of this qualitative study was to develop a social psychological explanation in the form of a substantive theory of how Ontario parents of children with autism navigate intervention under complex informational conditions. I used grounded theory methods, a constructivist approach and symbolic interactionist analytic framework for this research. The findings are primarily based on 45 in-depth (90-minute) interviews with 32 mothers from different urban and rural Ontario regions (fathers participated in 3 cases), and 9 professionals with expertise supporting parents. Documents were also analyzed. The central process of navigating intervention, labeled making your own way, consists of adjusting to the need to navigate intervention, in which parents construct the meanings that prepare and motivate them for taking action to navigate intervention. Adjusting consists of 4 interdependent sub-processes that together explain parents’ action: defining concerns, informing the self, seeing what is involved, and emotionally adapting. I portray the central process according to three overlapping heuristic stages: beginning the autism journey, handling transitions, and easing off. Many parents develop a strong sense of urgency to which they can respond by going into high gear, expending substantial personal resources sometimes at unsustainable rates in the pursuit of intervention. The findings have implications for supporting parents to improve outcomes including parent stress. The central process of making your own way is generically transferrable to other healthcare consumer populations. Other conceptual elements have theoretical relevance for consumer-centered areas of health research.
Keywords: autism; caregivers; information use; knowledge translation; grounded theory; qualitative research; health services research; system navigation; patient engagement; patient-centred care